THE EFFECTIVENESS OF LIBRARIANS' COMMUNICATION IN SOCIALIZING THE E-LIBRARY SYSTEM FOR STUDENTS OF THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA (UINSU): EFEKTIVITAS KOMUNIKASI PUSTAKAWAN DALAM MENSOSIALISASIKAN SISTEM E-LIBRARY PADA MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA (UINSU) - Suci Wahyu Tami Br Rambe; Abdul Karim Batubara; Elfi Yanti Ritonga (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the effectiveness of librarian communication in promoting the E-Library system to students at the State Islamic University of North Sumatra (UINSU) Medan. The focus of this research is to understand how librarians convey information about the features, benefits, and procedures for using the E-Library, as well as to identify challenges encountered during the socialization process. This research employs a qualitative approach using the field research method. Data were collected through in-depth interviews with the Head of the Library, library staff, and students who had participated in the E-Library socialization program. Additionally, non-participatory observation and documentation were utilized to complement the data obtained. Data analysis was conducted in three stages: data condensation, data display, and conclusion drawing. The findings reveal that the effectiveness of librarian communication in promoting the E-Library is influenced by the communication methods employed, such as the use of visual media and a personalized approach in delivering information. Challenges faced include limited digital collections, technical issues with the E-Library system, and students' low digital literacy. To address these issues, it is recommended that the library increase regular digital literacy training, expand the digital collection through partnerships with publishers, and improve the stability of the E-Library system. By implementing these measures, students are expected to be more encouraged to optimally utilize the E Library as a credible and high-quality source of religious information.